Objectiviser le subjectif pour l’imposer à l’autre : la « normativisation » de contenus évaluatifs comme procédé de modélisation argumentative de l’information sur Internet - Wołowska, Katarzyna (Studia Romanica Posnaniensia, 2017)
The aim of the article is to describe some semantic and argumentative mechanisms of Internet discourse processes whose role is to objectify the subjective evaluative judgments contained in the text so as to impose them as conforming to the socially accepted norm. The analyses are based on examples from French news websites available on the Internet.